Gambaran Kehamilan Berisiko Berdasarkan Usia Ibu: Literature Riview - Rini Gustina Sari; Oktri Ramadan; Conery Dery (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Pregnancy in women aged under 20 years and over 35 years is classified as a high-risk pregnancy because it may increase maternal and neonatal complications. This literature review aims to describe pregnancy risks based on maternal age, particularly among women younger than 20 years and older than 35 years. The method used was a literature review through the analysis of various scientific journals, articles, and health reports related to maternal age and pregnancy risks. The findings indicate that pregnancy in women under 20 years of age is associated with an increased risk of anemia, preterm birth, low birth weight, and maternal psychological unpreparedness. Meanwhile, pregnancy in women over 35 years of age is associated with hypertension, preeclampsia, gestational diabetes, cesarean delivery, and fetal chromosomal abnormalities. These risks are influenced by biological conditions, nutritional status, education, socioeconomic factors, and access to health services. Therefore, health education, routine antenatal care, and early detection of pregnancy risks are essential to reduce maternal and infant morbidity and mortality.